PELAKSANAAN PEMBELAJARAN PENDIDIKAN AGAMA ISLAM PADA LEMBAGA PENDIDIKAN NONFORMAL KEJAR PAKET C DI PKBM BUMI TULUNG SARADAN MADIUN - Eny Fatimatuszuhro Pahlawati; A. Syafi' AS. (Fakultas Agama Islam Universitas Darul 'Ulum Jombang, 2024)
This research aims to describe the Implementation of Islamic Religious Education Learning at Non-formal Education Institutions with the Package C Pursuit Program at PKBM Bumi Tulung Saradan Madiun This research is a type of qualitative research. Data collection uses observation, interviews and documentation methods. Meanwhile, the data analysis technique uses descriptive analysis. The research results show that there are several problems in implementing PAI learning. 1) inadequate facilities and infrastructure, 2) lack of subject hours, 3) the expertise of the tutors who teach is also not appropriate to the level they teach and 4) the diversity of students' religious knowledge considering the differences in their different backgrounds. The solutions to overcome these problems are: 1) planning, storing, arranging and deleting unused items, 2) making maximum use of time, 3) tutors should use the best possible methods so that students don't get bored and learning can be fun.